Rasio natrium karbonat dalam ekstraksi berpengaruh pada mutu natrium alginat sargassum muticum - Sovia Indah Nurkhanifah; Amir Husni (Jurnal Teknosains, 2020)
Brown seaweed is one of Indonesia’s biological resources which has good potential as source for alginate which can be used for the food and non-food industries. Alginate was most widely used in the textile sector around 50%, food industry 30%, paper industry 6%, welding rods 5%, pharmacy 5% and other 4%. The process of taking alginate from brown seaweed can be done by extraction. Several studies have been carried out in an effort to improve the yield of alginate extraction. The objective of this study was to determine the effect of the ratio of Na2CO3 and obtain the best ratio of Na2CO3 for producing sodium alginate from Sargassum muticum. The ratio of Na2CO3 used was 1:10, 1:20, 1:30, 1:40, 1:50 (w/v) and observations of alginate quality included yield (%), viscosity (cps), pH, water content (%), whiteness degree (%), ash content (%) and functional groups. The results showed that the higher the ratio of Na2CO3 produced the lower viscosity and showed significantly different values but yield, pH, water content, whiteness degree, and ash content were not significantly different. The functional groups at the ratio 1:20, 1:30, and 1:40 (w/v) showed the alginate that were in accordance with the standard. The best ratio of Na2CO3 from this study was 1:20 (w/v) because it had a medium viscosity, besides that, the yield, pH, water content, whiteness degree, and ash content also accordance to the quality of alginate standard.